Towards Green, Enhanced Photocatalysts for Hydrogen Evolution - Profumo, Antonella; Speltini, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book gathers selected research on the preparation, characterization and application of new organic/inorganic composites endowed with photo(electro)catalytic properties for the photocatalytic production of H2. In these pilot studies, the photoactive materials were tested under either UV-visible or, even more conveniently, under visible light for H2 evolution in "sacrificial water splitting" or "photoreforming" systems. In addition, a review article on the use of 2D materials and composites as potential photocatalysts for water splitting is included.